The effect of acute exercise on cognitive and motor inhibition – Does fitness moderate this effect?. (March 2023) - Netz, Yael; Herschkovitz, Saar Frank; Levin, Oron; Ziv, Gal
Abstract: Background: Given the extensive evidence on improvements in cognitive inhibition immediately following exercise, and the literature indicating that cognitive and motor inhibitory functions are mediated by overlapping brain networks, the aim of this study was to assess, for the first time, the effect of moderate intensity acute aerobic exercise on multi-limb motor inhibition, as compared to cognitive inhibition. Method: Participants were 36 healthy adults aged 40–60 years old (mean age 46.8 ± 5.7), who were randomly assigned to experimental or control groups. One-to-two weeks following baseline assessment, participants were asked to perform a three-limb (3-Limb) inhibition task and a vocal version of the Stroop before and after either acute moderate-intense aerobic exercise (experimental group) or rest (control). Results: Similar rates of improvement were observed among both groups from baseline to the pre-test. Conversely, a meaningful, yet non-significant trend was seen among the experimental group in their pretest to posttest improvement in both cognitive and motor tasks. In addition, exploratory analysis revealed significant group differences in favor of the experimental group among highly fit participants on the 3-Limb task. A significant correlation was indicated between the inhibition conditions, i.e., choice in the motor inhibition and color/word (incongruent) in the cognitive inhibition, especially in the improvement observed following the exercise. Discussion: Moderate-intensity acute aerobic exercise is a potential stimulator of both multi-limb motor inhibition and cognitive inhibition. It appears that high-fit participants benefit from exercise more than low-fit people. Additionally, performance on behavioral tasks that represent motor and cognitive inhibition is related. This observation suggests that fitness levels and acute exercise contribute to the coupling between cognitive and motor inhibition. Neuroimaging methods would allow examining brain-behavior associations of exercise-induced changes in the brain. Highlights: Inhibition is a key mechanism underlying cognitive and motor performance. Acute exercise improves movement inhibition tasks but not simple tasks. High-fit participants benefit from exercise more than low-fit people. The improvement in motor and cognitive inhibitions after exercise is related. This relationship is exhibited especially in the high-fit exercise group.